Kepemilikan Saham Asing, Manajerial, Institusional, Ukuran Perusahaan, dan Kinerja Lingkungan Terhadap Pengungkapan Laporan Berkelanjutan - Muhammad Faisal Arbain; Kusumawati, Eny (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
In the era of globalization and rapid information development, corporate social responsibility (CSR) has become a very important issue. One way for companies to demonstrate their commitment to sustainability is by disclosing sustainability reports. This study analyzes the effect of foreign share ownership, managerial, institutional, company size and environmental performance on SDGs disclosure in non-financial companies listed on the Indonesia Stock Exchange for the period 2021-2023. The sampling technique used in this study was purposive sampling. A total of 111 companies have met the criteria as observation units. The analysis method used is multiple linear regression analysis and has passed the classical assumption test. The results provide empirical evidence that only managerial share ownership variabels have a significant influence on SDGs disclosure. Meanwhile, foreign share ownership, institutional, company size, and environmental performance have no effect on SDGs disclosure. These findings provide important empirical and practical contributions for stakeholders, especially companies and policy makers, related to the factors that have contributions to the disclosure of SDGs (Sustainable Development Goals) in non-financial companies listed on the Indonesia Stock Exchange (IDX).